Redeployment of ophthalmologists in the United Kingdom during the Coronavirus Disease Pandemic. Issue 5 (September 2021) - Lim, Christina; De Silva, Ian; Moussa, George; Islam, Tahir; Osman, Lina; Malick, Huzaifa; Deol, Sundeep; Youssef, Moheeb; Farrag, Abdelsattar; Ashraf, Rehana; Burgula, Sreekala; Thompson, Jonathan
Background: During the current coronavirus (COVID-19) pandemic, some ophthalmologists across the United Kingdom (UK) have been redeployed to areas of need across the National Health Service (NHS). This survey was performed to assess aspects of this process including training & education, tasks expected, availability of personal protection equipment (PPE) used and the overall anxiety of ophthalmologists around their redeployment. Method: Online anonymous survey around the existing guidance on safe redeployment of secondary care NHS staff and PPE use by NHS England and Public Health England respectively. The survey was open to all ophthalmologists across the UK irrespective of their redeployment status. Findings: 145 surveys were completed and returned during a 2-week period between 17th April 2020 and 1st May 2020, when 52% of ophthalmologists were redeployed. The majority of this group consisted of ophthalmologists in training (79%). 81% of those redeployed were assigned to areas of the hospital where patients with confirmed Coronavirus disease were being treated as inpatients. There was a statistically significant improvement in anxiety level following redeployment which was mainly attributed to the support received by staff within the redeployed area. 71% of the redeployed group were found to have sufficient PPE was provided for the area they worked in. Interpretation: This is the first national survey performed on redeployment of ophthalmologists in the UK. The study showed that ophthalmologists across all grades were able to contribute in most aspects of patient care. Anxiety of redeployment was reduced by prior training and good support in the redeployment area.